PRAKTIK MONOPOLI PERUSAHAAN TELEKOMUNIKASI MILIK PEMERINTAH (STUDI KASUS PUTUSAN KPPU NOMOR 08/KPPU-I/2020) - Variza Octifanny Rahmadianti, (2022)
Netflix as a subscription-based digital streaming service provider has touched Indonesia since January 6, 2016. Only 3 (three) weeks after entering the Indonesian market, PT. Telkom Indonesia (Persero) Tbk. and PT. Telekomunikasi Seluler blocked internet access services for Netflix which is then indicated as a monopoly practice by PT. Telkom Indonesia (Persero) and PT. Telekomunikasi Seluler as the dominant telecommunications service provider in Indonesia. The research method used is a type of normative juridical research where data is taken based on a literature study using a case approach, a legal approach, and a conceptual approach. Based on the KPPU's consideration, PT. Telkom Indonesia (Persero) Tbk. and PT. Cellular Telecommunications is not proven to practice monopoly because monopoly is a special right granted by law to BUMN, making what was done by Reported Party I and Reported Party II right. Keywords: streaming services; monopoly practices; Internet.